The Jungian Gnosticism of the Ecclesia Gnostica - Hammer, Olav (International Journal for the Study of New Religions, 2018)
This article examines the ways in which Stephan Hoeller, head of the Ecclesia Gnostica, has transformed a very diverse set of late antique currents, with doctrines phrased in a mythic language unfamiliar to most moderns and rituals only sketchily documented in the sources, into a form of lived religiosity relevant for contemporary audiences.